Variation in Phomopsis azadirachtae, the incitant of die-back of neem - S. SHANKARA BHAT and K. GIRISH, SYEDA KOUSAR FATHIMA (Indian Phytopathology, 2004)
Six isolates of Phomopsis azadirachtae infecting neem collected from different districts of Karnataka State, South India were characterized based on cultural characteristics and their protein profile. Isolates varied significantly in colony colour, growth pattern and sporulation behaviour on potato dextrose agar medium. Mycelial proteins of these isolates exhibited significant variation in their electrophoretic pattern. The isolates from northern Karnataka shared close similarities among themselves in their protein profiles and differed with the isolates from southern Karnataka.